Optimization of Services Basic Education Data (Dapodik) - Agnia, Neneng Siti; Khumayah, Siti; Rahmayanti, Rahmayanti (Indonesian Journal of Advanced Research, 2025)
The Basic Education Data (DAPODIK) is a data collection system managed by the Ministry of Education and Culture that contains data on educational institutions, students, educators, educational staff, and educational content, with data sourced from educational institutions that is continuously updated online. The purpose of this study is to analyze and understand how the Basic Education Data (DAPODIK) service is provided at the Education Office of Majalengka Regency. This study uses a qualitative method. The study found that the lack of waiting areas often leads to congestion among service users. The Basic Education Data (DAPODIK) service lacks Standard Operating Procedures (SOP), inadequate service implementation, and a manual complaint system that requires a significant amount of time and does not provide an estimated timeframe for resolving user issues. From the research findings, it can be concluded that the Basic Education Data (DAPODIK) service at the Majalengka Regency Education Office is not operating at its full potential.